A new approach to the temporal significance of house orientations in European Early Neolithic settlements. - Nils Müller-Scheeßel; Johannes Müller; Ivan Cheben; Wiebke Mainusch; Knut Rassmann; Wolfgang Rabbel; Erica Corradini; Martin Furholt (PLoS ONE)
This paper shows that local differences in house orientation in settlements from the Early Neolithic in Central Europe reflect a regular chronological trajectory based on Bayesian calibration of 14C-series. This can be used to extrapolate the dating of large-scale settlement plans derived from, among other methods, geophysical surveys. In the southwest Slovakian settlement of Vráble, we observed a progressive counter-clockwise rotation in house orientation from roughly 32° to 4° over a 300 year period. A survey of published and dated village plans from other LBK regions confirms that this counter-clockwise rotation per settlement is a wider Central European trend. We explain this observation as an unintentional, unconscious but systematic leftward deviation in the house builders' cardinal orientation, which has been termed "pseudoneglect" in studies of human perception. This means that whenever houses were intended to be oriented towards a specific direction and be parallel to each other, there was an error in perception causing slight counter-clockwise rotation. This observation is used as a basis to reconstruct dynamics of Early Neolithic settlement in the Slovakian Žitava valley, showing a rapid colonization, followed by increased agglomeration into large villages consisting of strongly autonomous farmsteads.